Portugues (REMUNOM, 2024)
ABSTRACTThe article explores the complex relationship between man and mangroves in the neighborhoods of Chuabo Dembe, Sangariveira and Ícidia, in Quelimane, Mozambique. It examines the prevalent patterns of mangrove use and occupation, investigating the resulting environmental and socioeconomic impacts. The main objective is to pave the way for sustainable mangrove management practices, ensuring harmonious coexistence between communities and the mangrove. To uncover the complexities of mangrove use and occupation, the study employed a mixed methods approach, combining descriptive and explanatory elements. This approach involved collection and analysis of primary and secondary data. Primary data was collected through interviews with neighborhood secretaries, municipal authorities and environmental experts from the Ministry of Land and Environment of the Province of Zambézia. Secondary data were satellite images (Google Earth Engine), scientific articles, maps and technical reports. The study results paint a nuanced picture of interactions between neighborhoods and mangroves in the study area. While mangroves provide a multitude of benefits, including coastal protection, nutrient cycling and habitat provision, they also face significant threats from human activities. The study highlights the unsustainable exploitation of mangroves, driven by factors such as population growth, urbanization and demand for firewood, construction materials and land for agriculture. This exploitation manifests itself in several forms, including deforestation, dredging and conversion of mangrove areas into aquaculture ponds. In light of the alarming threats to mangroves, the study proposes a set of measures to promote sustainable mangrove management practices. These measures cover: Adaptation of environmental policies to the Mozambican context; Environmental Awareness Campaigns; development of sustainable income alternatives and ongoing monitoring and research.Keywords: Mangrove use and occupation; Environmental degradation; Sustainability; Environmental impacts of mangrove degradation